Alternative Development Strategies in SubSaharan Africa
XIV, 486 p.
Keywords: The World Bank and the IMF dominate policy-making in Africa today. This book considers the consistency between their adjustment policies and long-run development needs, with an analysis of country experience. An alternative development strategy is proposed.